Anti-Social Behavior Among Pakistani Students: Causes and Effects in the Light of Islamic Teachings (Al-Qamar, 2021)
There is a wide spread problem that ours in an era of violence and we are witnessing   an exceptional outburst of anti -social   behavior throughout the world. Young students are extensively discerned as being rowdy and anti- social as well as they commonly victimize of illegal activities. It is wide spread issue in all   societies is to have practices of   violence, aggression and   prejudicing behavior of young students.  It is experienced that sometime a person harms himself and sometimes other human being victimized. The question is what are   factors causing aggression and violence among the students? The answer to this question is there are some rationales; broken family, lack of guidance, weakening of the religious practices and ethical attitudes became main causes of this most thought full problem. Anti-social behavior is strictly prohibited by Allah Almighty in Islam and social harmony and peace is encouraged by equal measure. One of the reports in Bukhari(810AD-870AD) reports from Prophet of Islam, Muhammed (PBUH) A believer is he whose other believers remain safe from the wickedness of his hand and tongue. Islam has given great stress on keeping, promoting and encouraging peace and harmony and social leniency among the people. Because Islam gives complete code of life for character building of students and its social norms and values have great significance. As well as Islam demoralize violence in sura Baqarah (205) Wa Allahu la yuhibbu-al-fasad. The present paper will attempt to understand a study of causes and reasons of violence and aggression among the students which has become the pressing need of today owing to the escalation of extremism and violence in the world in the light of Islamic teachings.
Keywords: Aggression; harmony; Youth; Anti-Social; Islam